Education and Experience as Determinants of Micro Health Insurance Enrolment - Basri Savitha; Subrato Banerjee (Kerman University of Medical Sciences, 2021)
Background India faces a formidable challenge of providing universal health coverage to its uninsured population in the informal sector of the economy. Numerous micro health insurance (MHI) schemes have emerged as health financing mechanisms to reduce medical-illness-induced poverty. Existing research shows that the purchase of health insurance is most likely to be determined by health status, expected healthcare expenditure, and past health experiences in addition to socio-economic variables. We add to the understanding of various factors influencing enrolment in MHI from an Indian perspective.   Methods A survey was carried out to collect quantitative data in three districts in the state of Karnataka, India.   Results We show that education does not matter as significantly as experience does, in the determination of new insurance purchases. In other words, the importance of new insurance is not understood by those who are merely educated, but by those who have either fallen ill, or have previously seen the hazards of usurious borrowing.   Conclusion Our study provides deeper insights into the role of usurious borrowing and past illness in determining insurance purchases and highlights the formidable challenge of financial sustainability in the MHI market of India.